The Effect Of Breastfeeding And Partnership Exercise On The Decrease Of The Height Of The Uterial Funds Of The Mother Post Partum In The Delivery Room - Neny Marwiyah (Chakra Brahmanda Lentera Institute, 2020)
The slow decrease in uterine fundal height is a problem that often occurs in mothers after childbirth or the puerperium, so that bleeding can occur and result in maternal death during the puerperium. Post Partum Mother in the Maternity Room UPTD Timbulon Health Center, West Paleleh District, Buol Regency. The design used in the study was a pre-experimental one group pre-test-post test. The population is all post partum mothers with normal parturition. The sample size is 30 respondents using simple random sampling technique. The independent variables of the study were breastfeeding and postpartum exercise. The dependent variable was uterine fundal height. Data was collected using a questionnaire, after the mother gave birth on day 1, the uterine fundal height was measured using a new middle measuring instrument and recorded on the observation sheet, then on the 6th day the uterine fundal height was measured again. The data were analyzed using the Wilcoxon test, with a significance level of 0.05. The results showed that the most respondents had pre-intervention TFU, which was 12 cm, as many as 14 respondents (46.7%), and post-intervention TFU, which was 8 cm, with 11 respondents (36.7%). The results showed that p = 0.000 with a <0.05, which means that there is an effect of breastfeeding and postpartum exercise on the acceleration of the decrease in uterine fundal height for post partum mothers in the UPTD Maternity Room, Timbulon Public Health Center, Paleleh Barat District, Buol Regency. Breastfeeding and Postpartum Gymnastics can accelerate the decrease in the height of the uterine fundus in postpartum mothers because of the response of the muscles that experience stretching during pregnancy and childbirth, so that the height of the uterine fundus quickly returns to normal as before.